Computational exploration of simulations in political science. - Crouser, R. Jordan.; Freeman, Jeremy G.; Chang, Remco. (Tufts University. Tisch Library., 2017)
A novel method of constructing graphs of agent-based simulation data enables social scientists to better understand complex systems.